JASA PENYEDIAAN BIODIVERSITAS PADA SISTEM AGROFOREST KALIWU - Gerson N. Njurumana (Jurnal Pemuliaan Tanaman Hutan, 2019)
Biodiversity has a strategic role in socio-economic aspect, especially the provision services to humans and the surrounding ecosystem. Diverse of provision services encourage people to manage biodiversity in the cultivation environment, one of which is Kaliwu Agroforests. Kaliwu Agroforest, is a multi-species based of dryland farming model, developed by local communities in Sumba island to support various of provision services to the communiies, one of which is food. Recently, data and information about food crop species biodiversity in Kaliwu agroforests, and their contribution to meet the food needs to the local communities are not available. Understanding the biodiversity species of food crops in Agroforest Kaliwu and its contribution to household food needs is required. Therefore, field observations and interviews to 70 households of Kaliwu agroforest owners in Central Sumba District were carried out. Data and information obtained were analyzed descriptively and qualitatively. The results of analysis showed, the plants biodiversity of food source in Kaliwu Agroforests is varies. There are 12 species of food sources from the cassava group, and 46 species from the fruits group. Each farmer has different biodiversity of food crops species, and is determined by the choices and decisions of the farmers to cultivate. Farmers decision influenced the variations of tubers and fruits contribution in cultivate the Kaliwu agroforest. Contributions of foodstuffs per capita needs of tubers ranges from 35-41%, while for the group of fruits range from 55-81%. Referring to the species variety and its contribution value, Kaliwu Agroforest has a significant role to support the biodiversity conservation and fulfilment the food needs to the local communities. It is needed to encourage and empower the local potential agroforests an alternative to build community-based food security, such as Kaliwu Agroforest that provide added value, and increase food self-sufficiency and security in the local communities